Pediatric full-thickness burns by cyanoacrylate nail glue: A case report - Sarthak Aggarwal; Sachin Aggarwal; Rashmi Aggarwal (Elsevier, 2021)
Cyanoacrylate-based adhesives react aggressively with cotton in a highly exothermic manner. These adhesives are widely available, but the dangers of such glues in producing severe burns are still poorly understood, especially in pediatric populations. There are few case reports examining full-thickness burns resulting from nail glues (a cyanoacrylate-based adhesive), which are often stored in bottles lacking robust safety mechanisms. As a result, there is a lack of understanding by both the general populace and medical community of the severe consequences of such glues contacting cotton-based clothing in both adults and children. Here we present a case of full-thickness burns on the dorsal aspect of the foot of a two-year-old male who spilled nail glue on his sock. The resultant reaction rapidly produced three adjacent burns. The wound required consistent management and healed almost completely after 9 weeks. We aim to raise awareness of full-thickness burns resulting from nail glue spills, as well as to draw attention to the need for better warnings and safety features on glue bottles. We also hope to highlight best practices for the treatment of such burns.